Vaginal microbiota and persistence of human papillomavirus infection (Research, Society and Development, 2022)
The vaginal microbiota is composed of a diversity of microorganisms that inhabit the vagina, either permanently or transiently. There are many questions about what could cause a disruption in the vaginal balance with regard to bacterial composition, inflammation, pH change and secretion of substances (cytokines and enzymes). In addition, it is already established that bacterial vaginosis can predispose to HPV infection, its persistence and the development of precursor lesions of cervical cancer. The aim of this study was to elucidate the correlation between the vaginal microbiota and the persistence of HPV infection. This is a comprehensive literature review using the Medline/PubMed and Web of Science Databases published from 2010 to 2021. It was identified that bacteria related to Bacterial Vaginosis (CST IV) and CST III, dominated by L. iners, had a greater dominance in HPV-positive women and may be related to HPV acquisition and persistence. The presence of Sneathia, found in the vaginal microbiota of HPV-positive women, suggests a relationship with viral persistence and cervical intraepithelial neoplasia (CIN).